Effect of antiretroviral therapy on progression of endothelial dysfunction in acquired immune deficiency syndrome patients - Varte, Zorinsangi; P., Naveen; Ralte, Wendy L. (International Journal of Research in Medical Sciences, 2019)
Background: Though the natural history of Human Immunodeficiency Virus (HIV) infection in many patients has been dramatically altered through the use of antiretroviral therapy, this treatment paradigm of chronic chemotherapy may not be sustainable given the short and long-term toxicities of these medications. Currently, there is lack of data in the Indian literature regarding study of endothelial dysfunction in HIV patients. The purpose of our research was to study the effect of anti-retroviral therapy on the progression of endothelial dysfunction in HIV/AIDS patients. Methods: The study comprises a total number of 30 adult HIV positive patients of both sex with confirmed HIV seropositivity and CD 4+T cell count < 200/µl. None of these patients had ever received anti retroviral therapy (ART). These patients were subjected to detailed clinical examination and markers of endothelial dysfunction - Flow mediated vasodilatation (FMD) of brachial artery, S. Nitrite and C-reactive protein (CRP) were performed before starting ART. Study group patients were started on ART, they received triple drug ART (Lamivudine 150 mg BD, Stavudine 30 mg BD, Nevirapine 200 mg BD). In patients on ART after a period of 6 months, markers of endothelial dysfunction - FMD, S. Nitrite and CRP tests were reassessed. Results: FMD (4.08±3.58) and S. Nitrite (20.83±13.75) were also depressed after six months of anti retroviral therapy. Also, patients showed more CRP positivity and higher titres after ART. CD 4+T cell count before ART (124.16±84.46) and after ART (186.63±70.96). This rise in count was statistically significant. Conclusions: HIV patients who are receiving ART demonstrate a number of metabolic abnormalities with more severe depression in markers of endothelial function.